Association of Total Dietary Intake of Sugars with Prostate-Specific Antigen (PSA) Concentrations: Evidence from the National Health and Nutrition Examination Survey (NHANES), 2003-2010. (9th January 2021) - Liu, Zhangcheng; Chen, Chi; Yu, Fuxun; Yuan, Dongbo; Wang, Wei; Jiao, Ke; Yang, Shengbang; Zhang, Yongqiang; Wang, Yong; Liu, Linhai; Xu, Huali; Zhang, Yang; et al.
Abstract : Background . There is increasing evidence that dietary intake of sugars may be a risk factor for prostate cancer (PCa) and elevate the concentration of serum prostate-specific antigen (PSA). However, there is limited evidence of the correlation between total dietary intake of sugars and serum PSA concentrations for adult American males. Herein, we evaluated the association between total dietary intake of sugars and serum PSA concentrations in men without a malignant tumor diagnosis in the United States (US) National Health and Nutrition Examination Survey (NHANES) database. Material and Methods . In this secondary data analysis, a total of 6, 403 men aged ≥40 years and without malignant tumor history were included from 2003 to 2010. The independent variable of this study was the total dietary intake of sugars, and the dependent variable was serum PSA concentrations. Covariates included dietary, comorbidity, physical examination, and demographic data. Results . The average age of participants included in this study was 58.1 years (±13.6). After adjusting for the dietary, comorbidity, physical examination, and demographic data, we observed that a dietary intake increase of one gram of total dietary intake of sugars was associated with an increase of serum PSA concentrations by 0.003 ng/mL (after log2 transformed, 95% CI: 0.001 to 0.005) with a P value for trend less than 0.05. Sensitivity analysis using the generalized additive model (GAM) supported the linear association between total dietary intake of sugars and serum PSA concentrations. Conclusion . The total dietary intake of sugars is independently and positively associated with serum PSA concentrations in adult American males who are without a personal history of malignant tumors.